Development of Image Processing to Visualize Car Dimensions Using Matlab Software - Miranda Julianti; Ony Hizri Kaifa Purba; Putri Aisyah Sephia (Ali Institute of Reseach and Publication, 2023)
In an era of increasingly advanced technology, the development of image processing techniques has become important in various fields, including the automotive industry. One important aspect in the automotive industry is understanding and visualizing car dimensions with high accuracy. In this research, we propose the development of image processing techniques using MATLAB software to visualize car dimensions. The proposed method involves a series of image processing steps, including car object segmentation, binary image, and image editing. First, the car image is imported into MATLAB software and converted into a grayscale image. Next, segmentation of the car object is carried out using an appropriate threshold technique. Next, the feature extraction results are used to visualize the dimensions of the car. This visualization can be in the form of a 2D diagram that displays the dimensions of the car proportionally, or a 3D model that shows a three-dimensional view of the car. Through this visualization, users can easily see and understand the dimensions of the car without the need for complicated manual measurements.